2016
DOI: 10.3122/jabfm.2016.06.160092
|View full text |Cite
|
Sign up to set email alerts
|

Physician Advice for e-Cigarette Use

Abstract: Purpose: The purpose of this study was to determine characteristics of smokers discussing e-cigarette use with their physician and receiving physician recommendations to use e-cigarettes for smoking cessation. Methods: Data were collected from surveys of an online consumer panel of US adult smokers who had visited a physician in the previous 12 months (n=2,671). Logistic generalized estimating equation (GEE) models were used to assess the characteristics of smokers who: 1) talked to a physician about e-cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…26 Marketing contributes to perceived knowledge regarding the health and safety of e-cigarettes 28 , and in our sample, participants heard about e-cigarettes from the media, family or friends, and e-cigarette (vape) shops, but very few heard about them from physician offices, which is consistent with other research. 29 These findings underscore the need for PCPs to be able to provide patients with accurate information on these products rather than relying on potentially biased and profit-driven sources of information.…”
Section: Discussionmentioning
confidence: 99%
“…26 Marketing contributes to perceived knowledge regarding the health and safety of e-cigarettes 28 , and in our sample, participants heard about e-cigarettes from the media, family or friends, and e-cigarette (vape) shops, but very few heard about them from physician offices, which is consistent with other research. 29 These findings underscore the need for PCPs to be able to provide patients with accurate information on these products rather than relying on potentially biased and profit-driven sources of information.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have indicated that dialogues about NVPs have become increasingly frequent in clinical settings , are generally initiated by the patient , and typically do not end in a recommendation to use NVPs, apparently because most providers remain neutral or advise against use . To the best of our knowledge, only two studies have examined patient–physician NVP discussions from the patient's perspective . One online study in the United States by Berg et al .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current study, moreover, clinical advice and public health efforts to reduce illness related to smoking may need to be aware of different beliefs in different parts of the country so as to be able to effectively tailor messages. A national online study of smokers conducted in a similar timeframe as the 2015 TUS‐CPS data collection found that 15% of respondents discussed e‐cigarettes with their physicians, among whom 61% were advised to try e‐cigarettes as a smoking cessation aid . With reduced access to health care in rural areas, the burden for education falls more heavily on public health and policy advocates, distinguishing messages for never, current, and former smokers to maximize public health benefits …”
Section: Discussionmentioning
confidence: 99%
“…A national online study of smokers conducted in a similar timeframe as the 2015 TUS-CPS data collection found that 15% of respondents discussed e-cigarettes with their physicians, among whom 61% were advised to try e-cigarettes as a smoking cessation aid. 43 With reduced access to health care in rural areas, 9 the burden for education 25 falls more heavily on public health and policy advocates, distinguishing messages for never, current, and former smokers to maximize public health benefits. 44 There are several important factors that may affect developing patterns of e-cigarette use and beliefs in rural regions.…”
Section: Discussionmentioning
confidence: 99%